A STUDY ON STUDENTS’ NEEDS ANALYSIS ON THE INDUSTRIAL WORK CULTURE CHARACTER - Arhamni Hamid; Zahari Supaian; Anwar Ramli; Saifullah Idris (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Character has become a requirement that must be paid attention to in learning in vocational schools. However, the development of an instrument to assess the character of students in vocational schools is not yet available. The purpose of this study is to explain the need for analysis of the design of a character assessment instrument for SMK students in Aceh who are preparing to work in the industrial world. Character is a set of traits that define personality and morals. This study aims to describe the analysis of the planning needs of the industrial work culture character assessment instrument (IKBKI) for SMK Aceh students in implementing the industrial work culture character assessment. Data was obtained through a survey of 65 SMK students in Aceh who were given a questionnaire followed by a brief interview. The sample involved is 65 SMK students in Aceh. Students are selected with a purpose. Questionnaires were distributed to all students selected as a sample. The questionnaire was developed by the researcher. Data were analysed using Statistical Package for Social Science (SPSS) version 25.0 software for frequency, percentage, mean, and standard deviation. The results of the study show that the work culture character instrument (IKBKI) is needed to assess the development of the industrial work culture character of SMK Aceh students. The characteristics of industrial work culture that are evaluated are discipline, hard work, honesty, responsibility, and entrepreneurial spirit. The result of the needs analysis obtained is that students need an assessment of the character of industrial work culture as a reference in preparing themselves to enter the world of work and industry. Students’ understanding of the need to have good manners has been taught by teachers in character education strengthening programs and also through Pancasila moral education and the Pancasila Work Culture and Student Profile Strengthening Project, but the character of industrial culture has never been studied specifically. Because this instrument is not yet available, the assessment of the character of the industrial work culture has not been carried out, so it cannot be concluded whether the character of the industrial work culture of students who have completed vocational education so far is on target. whether it is good or not, or whether it meets the expectations of government and industry as users of the service. The character of industrial work culture is something that is an important and necessary consideration in the industrial world, known as attitude. The results of the preliminary study show that there is no instrument to assess the character of industrial work culture. On the other hand, the government and industry hope that students will be equipped with good morals when entering the world of work. On this basis, it can be concluded that it is necessary to design the Industrial Work Culture Instrument (IKBKI).